Eksplorasi Tabebuya sebagai Sumber Ide pada Desain Motif Batik Tanah Unesa - Rochmawati, Zulfika; Russanti, Irma (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
Tabebuya has a distinctive beauty, attractive shapes and colors that can be applied in Unesa soil batik coloring. This research uses the Double Diamond approach. This method consists of 4 stages Discover, Define, Develop, and Deliver. In the early stages of identifying the facts of the problem in the form of a lack of development of Surabaya city flora motifs in Batik Tanah Unesa. The second stage, analyzing researchers who have been identified at the discovery stage is in the form of a moodboard. The third stage, embodiment where the design idea has been generated will be shaped into a work. Followed by the last stage of the manufacturing stage and design selection from the solutions that have been obtained from the previous stage. The process of developing motifs starts with preparing tools and materials, then the process is drawing designs on paper, followed by tracing on cloth, and on batik so that the finished result appears on the cloth. The result of the expected batik motif is the result of the batik motif in accordance with the size of the motif design, starting from the main, supporting, and isen motifs according to the source of the Tabebuia idea.